Building and Testing an Evaluation Model of the Impact of Cycling Policies. (June 2017) - Boig, Ester Anaya; de Nazelle, Audrey; Götschi, Thomas; Gerike, Regine; Pierotti, Livia; Kahlmeier, Sonja; Cole-Hunter, Tom; Nieuwenhuijsen, Mark; Int Panis, Luc; Rojas-Rueda, David; Avila-Palencia, Ione
Abstract : Background: In order to increase the levels of physical activity in urban population, it is essential to evaluate how real-life policy interventions affect the population cycling attitudes and behaviour. There is evidence to support that policies of different nature have the potential to influence cycling behaviour, but few studies have done longitudinal and multiple interventions assessments. Methods: As part of the PASTA European project (Physical Activity through Sustainable Travel Approaches), a longitudinal survey in 7 European cities provides data for the analysis. The questionnaires in the survey feature socio-demographic, psycho-social and city-specific policy-related questions. For each of the 7 cities, a selection of the highest impact policy measures implemented during the survey (November 2014 – January 2017) has been made. The effect of the policy interventions is studied as a natural experiment, with exposed and non-exposed population based on the distance to the infrastructure. The study includes unique a dose-response function which considers the exposure to multiple interventions, the technical quality of these interventions and an adapted bikeability index associated to each participant in each time stamp. Results: Our sample includes 10, 557 participants across the seven cities. Results will be shown for the complete dataset. Preliminary results from the initial questionnaire (baseline) are already available. A substantial part of the participants are initially either non-cyclists (24%) or cycling less than once a month (23%), which means that 47% of the sample could potentially start cycling or increase their frequency. Furthermore, 52% of the participants intend to increase their cycling rates in the future. All the cities have selected "top measures" and details are being collected. Measures range from bike to work campaigns, to cycle superhighways or other built environment interventions. For example, we have an estimate of a 36% of the participants in London being exposed to any kind of cycling policies. Once the evaluation model will be applied, results will show which profiles of participants are influenced by which types and dose of policies in their attitudes and decisions around cycling for transport. Conclusions: The PASTA project explores the bridges between science and policymaking. This study develops and tests an innovative evaluation model which seeks to account for the impact in cycling behaviour of multiple interventions and for the quality of the build environment and interventions themselves. The relation between cycling policies and cycling behavioural aspects will help to determine the most promising policy avenues to promote cycling.